Unexpected Cartilage Phenotype in CD4-Cre-Conditional SOS-Deficient Mice - Guittard, Geoffrey; Gallardo, Devorah L.; Li, Wenmei; Melis, Nicolas; Lui, Julian C.; Kortum, Robert L.; Shakarishvili, Nicholas G.; Huh, Sunmee; Baron, Jeffrey; Weigert, Roberto; Kramer, Joshua A.; Samelson, Lawrence E.; et al. (Frontiers in Immunology, 2017)
RAS signaling is central to many cellular processes and SOS proteins promote RAS activation. To investigate the role of SOS proteins in T cell biology, we crossed Sos1f/f Sos2-/- mice to CD4-Cre transgenic mice. We previously reported an effect of these mutations on T cell signaling and T cell migration. Unexpectedly, we observed nodules on the joints of greater than 90% of these mutant mice at 5 months of age, especially on the carpal joints. As the mice aged further, some also displayed joint stiffness, hind limb paralysis and lameness. Histological analysis indicated that the abnormal growth in joints originated from dysplastic chondrocytes. Second harmonic generation imaging of the carpal nodules revealed that nodules were encased by rich collagen fibrous networks. Nodules formed in mice also deficient in RAG2, indicating that conventional T cells, which undergo rearrangement of the T cell antigen receptor, are not required for this phenotype. CD4-Cre expression in a subset of cells, either immune lineage cells (e.g. non-conventional T cells) or non-immune lineage cells (e.g. chondrocytes) likely mediates the dramatic phenotype observed in this study. Disruptions of genes in the RAS signaling pathway are especially likely to cause this phenotype. These results also serve as a cautionary tale to those intending to use CD4-Cre transgenic mice to specifically delete genes in conventional T cells.